The influence of customer experience on repurchase intention at tekun.id beverage outlets - Yusuf Tojiri; Jajang Sugiat (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of customer experience on repurchase intention at Tekun.Id beverage outlets. The research method used is descriptive and associative methods with data collection through surveys using questionnaires. Research respondents are Tekun.Id customers who have made previous purchases. The results of data analysis using SPSS software show that customer experience has a positive and significant influence on repurchase intention. These findings highlight the importance of service quality, positive interactions, and visual elements such as drink color in creating a positive customer experience. Strategic implications involve expanding loyalty programs, improving service quality, and focusing on visual innovation to increase customer retention. The conclusions of this research provide an in-depth understanding of the relationship between customer experience and repeat purchase decisions, which can be a valuable guide for companies in optimizing their marketing strategies.